Increasing Digital Literacy In Education: Analysis Of Challenges And Opportunities Through Literature Study - Kardina Engelina Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
By conducting literature research, this research aims to evaluate the difficulties and prospects in increasing digital literacy in education. In today's digital era, digital literacy is becoming increasingly important. The ability to understand, use and participate in digital environments is essential. However, the development of technology and its use in education also raises complex problems. Literature analysis was carried out to identify the main problems faced by students and teachers in improving digital literacy. The results of the analysis show that some of the main problems include the pace of change in digital technology, lack of access to technology, inappropriate curriculum, lack of teacher training, and inequality. On the other hand, there is a huge opportunity to improve digital literacy. This can be achieved through developing a curriculum that is integrated with technology, increasing accessibility to digital infrastructure and devices, and ongoing training for educators. A better understanding of the complexities of difficulties and opportunities in improving digital literacy among students and educators is gained from this research. It is hoped that this research will make a positive contribution to the continued progress of education in the computer and internet era because these findings can help create more efficient educational policies and teaching strategies that take advantage of developments in digital technology.